LINEAR HIERARCHY REGRESSION USING SLICE SAMPLING MARKOV CHAIN MONTE CARLO - Fibia Sentauri Cahyaningrum; Nola Riwibowo; Wahyu Tri Prambudi; Menik Ariyanti (Smart Education, 2026)
Abstract: Multilevel regression analysis is a regression analysis that assumes there is data that has a hierarchical structure with one response variable measured at the lowest level and predictor variables at various levels. The simplest multilevel linear regression model consists of 2 hierarchical levels, where level 1 is the lowest level data, and level 2 is the data that has a higher level. The Human Development Inde HDI is one indicator that can be used to measure the success of a particular country or region in efforts to improve the quality of life of its population. This study aims to determine the factors that influence the HDI in East Java, Central Java, and West Java. The data used in this study are the HDI, per capita expenditure adjusted at the district or city level categorized at level 1, while the growth rate of Gross Regional Domestic Product GRDP at the provincial level categorized at level 2. The results of the multilevel linear regression analysis indicate that the variables of per capita expenditure and GRDP growth rate significantly influence the HDI in East Java, Central Java, and West Java. Keywords: GDRP, HDI, MCMC, Multilevel Regression, Per Capita Expenditure, Slice Sampling. Abstrak: Analisis regresi multilevel adalah analisis regresi yang mengasumsikan adanya data dengan struktur hierarkis, di mana satu variabel respons diukur pada tingkat terendah dan variabel prediktor berada pada berbagai tingkat. Model regresi linear multilevel yang paling sederhana terdiri dari dua tingkat hierarkis: tingkat 1 merupakan data pada tingkat terendah, sedangkan tingkat 2 merupakan data pada tingkat yang lebih tinggi. Indeks Pembangunan Manusia (IPM) merupakan salah satu indikator yang dapat digunakan untuk mengukur keberhasilan suatu negara atau wilayah dalam upaya meningkatkan kualitas hidup penduduknya. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang memengaruhi IPM di Jawa Timur, Jawa Tengah, dan Jawa Barat. Data yang digunakan dalam penelitian ini meliputi IPM serta pengeluaran per kapita yang disesuaikan pada tingkat kabupaten/kota (dikategorikan sebagai tingkat 1), sedangkan laju pertumbuhan Produk Domestik Regional Bruto (PDRB) pada tingkat provinsi dikategorikan sebagai tingkat 2. Hasil analisis regresi linear multilevel menunjukkan bahwa variabel pengeluaran per kapita dan laju pertumbuhan PDRB berpengaruh signifikan terhadap IPM di Jawa Timur, Jawa Tengah, dan Jawa Barat. Kata kunci: GDPR, HDI, MCMC, Regresi Multilevel, Pengeluaran Per Kapita, Pengambilan Sampel Irisan.